Transcription factor E3 protects against cadmium-induced apoptosis by maintaining the lysosomal-mitochondrial axis but not autophagic flux in Neuro-2a cells. (1st October 2018) - Pi, Huifeng; Li, Min; Xie, Jia; Yang, Zhiqi; Xi, Yu; Yu, Zhengping; Zhou, Zhou
Graphical abstract: Highlights: Cd-induced Neuro-2a cells apoptosis was via the lysosomal-mitochondrial axis. Cd activated TFE3 nuclear translocation was linked to lysosomal stress in Neuro-2a cells. Tfe3 overexpression maintained the Cd-disrupted lysosomal-mitochondrial axis in Neuro-2a cells. Tfe3 overexpression did not restore the Cd-impaired autphagic flux in Neuro-2a cells. Abstract: Cadmium (Cd), is a well-known environmental and occupational hazard with a potent neurotoxic action. However, the mechanism underlying cadmium-induced neurotoxicity remains unclear. Herein, we exposed Neuro-2a cells to different concentrations of cadmium chloride (CdCl2 ) (12.5, 25 and 50 μM) for 24 h and found that Cd significantly induced lysosomal membrane permeabilization (LMP) with the release of cathepsin B (CTSB) to the cytosol, which in turn caused the release of mitochondrial cytochrome c (Cyt c) and eventually triggered caspase-dependent apoptosis. Interestingly, Cd decreased TFE3 expression but induced the nuclear translocation of TFE3 and TFE3 target-gene expression, which might be associated with lysosomal stress mediated by Cd. Notably, Tfe3 overexpression protected against Cd-induced neurotoxicity by maintaining the lysosomal-mitochondrial axis, and the protective effect of TFE3 is not dependent on the restoration of autophagic flux. In conclusion, our study demonstrated for the first time that lysosomal-mitochondrial axis dependent apoptosis, a neglected mechanism, may be the most important reason for Cd-induced neurotoxicity and that manipulation of TFE3 signaling may be a potential therapeutic approach for treatment of Cd-induced neurotoxicity.